Institutional frameworks to facilitate power sector transformation in West Africa - Tam Kemabonta; Nathan G. Johnson (Energy Strategy Reviews)
The African Single Electricity Market aims to create the world's largest electricity market by 2040. This initiative faces the challenge of interconnecting a continent with significant geographical, cultural, and political differences, and addressing energy poverty for over 500 million people. This paper examines these challenges within the 14 member states of the West African Power Pool and offers foundational knowledge at the interface between local utilities and the proposed continent-wide grid. A historical review of electrical power sector reform in the region is completed, with findings showing modest effect on energy access and operational efficiency in the region, which is almost negligible after accounting for population growth across Africa. Reform efforts based on the Washington Consensus are found to have minor or mixed success due to implicit assumptions that do not relate well to Sub-Saharan Africa. Other reform approaches are introduced and contrasted for application to the West African Power Pool, including the Willing Buyer Willing Seller, product differentiation, operational flexibility, decentralized and community energy planning, and contestability in local electricity markets. Such frameworks provide adaptation to local conditions, experimentation and learning, increased transparency, more flexible ownership models, reduced exposure to risk, and flexible institutional mechanisms that can evolve as the power sector develops in the West African Power Pool and across Africa generally.